CP-103 Subcutaneous single-use injection device and intravenous formulations in patients with HER2-positive early breast cancer. (24th February 2014) - Martin Nuñez, I; Lopez-Vivanco, G; Salvador, J; Porras, I; Ramirez, C
Abstract : Background: Trastuzumab is a HER2-specific monoclonal antibody infused intravenously (IV) over 30 min. A new fixed-dose subcutaneous (SC) formulation enables trastuzumab to be delivered over 5 min without compromising its efficacy and safety. It is unclear to what extent the new formulation is time-saving for healthcare practitioners (HCP) or patients and how saving time might translate into saving money. Purpose: To describe HCP and patient time and related costs associated with IV and SC trastuzumab formulations in patients with HER2-positive early breast cancer. Materials and methods: Prospective, observational time and motion study in 3 Spanish centres performed as a substudy of the PrefHer trial. We recorded HCP active time for SC and IV-related tasks and calculated HCP time as the mean sum of task times over 154 administration episodes (80 IV, 74 SC). We calculated mean patient time in the treatment room and the infusion chair. Staff costs were calculated using fully loaded salary costs based on Spanish salaries (€2012). Results: The transition from IV to SC trastuzumab led to a 50% reduction of active HCP time (27.2 min (95% CI:21.8–32.6) vs. 13.2 min (95% CI:8.9–17.5) per cycle). Time savings resulted from not needing to insert or remove the IV catheter, line flushing and drug reconstitution. SC administration led to a 5-fold reduction (78–85%) in chair time and to a 4-fold reduction (59–81%) in patient time in the treatment room equating to a total of 24 h freed time in total treatment course (18 cycles). Staff costs for observed tasks were 12.6 € and 5.9 € per cycle for IV and SC, respectively, indicating a saving of 120 € over a full treatment course. Conclusions: SC trastuzumab provided substantial time savings for HCP and patients, meaning reduced staff costs versus IV trastuzumab. Reducing the use of hospital facilities may result in further savings. No conflict of interest.